Discrimination and disparities - Sowell, Thomas (New York Basic Books, 2018)
Economic and other outcomes differ vastly among individuals, groups, and nations. Many explanations have been offered for the differences. Some believe that those with less fortunate outcomes are victims of genetics. Others believe that those who are less fortunate are victims of the more fortunate.
Includes bibliographical references and index.
Keywords: Economic policy